Pengembangan Kewirausahaan Tenun sebagai Upaya Pemberdayaan Masyarakat Bayan, Lombok - Muryanti, Muryanti; Sulistyaningsih, Sulistyaningsih; Hanjarwati, Astri (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2024)
Bayan Village has cultural value related to weaving production, which can be developed into tourism. This research aims to find out how social entrepreneurship is owned by the community in preserving and developing weaving businesses and to find out how the empowerment process is in Bayan Village. The research method is qualitative using interviews and observation to obtain primary data. The theory used is community empowerment carried out by stakeholders to preserve and develop weaving as a traditional cloth and the traditional wealth of the Bayan Village community. The research results show that existing entrepreneurship is still traditional with simple forms of business, local in nature, prioritizing wisdom and preserving culture. Increasing entrepreneurship is carried out through empowerment carried out by the village government, tourism service, trade service, community leaders, and UNESCO in various ways, including providing development funding assistance for weaving production, assisting weaving production by organizing various kinds of exhibitions held at the hamlet level up to provincial which is held in the provincial capital; various kinds of training related to weaving in the form of thread selection, natural dyeing, introduction to looms from India which are different from those in Indonesia and training in making motifs. Sustainable empowerment is carried out by providing education and training in weaving skills with motifs characteristic of Bayan Village. How children can become skilled at weaving is part of the curriculum and extra-co-curricular activities at school. Apart from school, children practice weaving in community groups after school to practice their skills and increase their income. The hope is that these various types of entrepreneurial efforts can improve community welfare.